2005
DOI: 10.1007/s11017-005-7946-0
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Out the Concept Disorder

Abstract: Current debates concerning the concept of mental disorder involve many different philosophical issues. However, it is not always clear from these discussions how, or whether, these issues relate to one another, or in exactly what way they are important for the definition of disorder. This article aims to sort through some of the philosophical issues that arise in the current literature and provide a clarification of how these issues are related to one another and whether they are necessary for defining disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…Kelly and Westerhoff [64] found that referring to an individual as a "substance abuser" as opposed to an individual with a "substance use disorder" enables stigmatizing attitudes relating to perceptions that individuals labeled "substance abusers" are willfully deviant. Receiving a psychiatric diagnosis, or even a label-as 'brain diseased' or otherwise-carries a value [65]. Values permeate the diagnosis, labels, biolooping effects [63], and their collective meaning in the human life-world [62].…”
Section: The Paradoxmentioning
confidence: 99%
“…Kelly and Westerhoff [64] found that referring to an individual as a "substance abuser" as opposed to an individual with a "substance use disorder" enables stigmatizing attitudes relating to perceptions that individuals labeled "substance abusers" are willfully deviant. Receiving a psychiatric diagnosis, or even a label-as 'brain diseased' or otherwise-carries a value [65]. Values permeate the diagnosis, labels, biolooping effects [63], and their collective meaning in the human life-world [62].…”
Section: The Paradoxmentioning
confidence: 99%
“…The two major contemporary philosophical positions in demarcating disorder are "naturalism" and "normativism." 2 It is difficult to adequately summarize these competing definitions as they constitute an entire field of philosophical analysis (see Bolton, 2001Bolton, , 2008Ereshefsky, 2009;Murphy, 2009;Ross, 2005Ross, , 2007. Nonetheless, naturalism treats disorder as an objective property, something independent of value judgments and of culture and can be discovered through the scientific method (e.g.…”
Section: The Philosophy Of Defining Disordermentioning
confidence: 99%
“…Since the 1970s, with concerns over the status of psychiatry within medicine, and anti-psychiatry critiques over how psychiatry sought to justify what it treated, significant attention has been given to how to demarcate disorder from non-disorder, 1 and this is what prompted Engel’s call for a more comprehensive model of illness. The two major contemporary philosophical positions in demarcating disorder are “naturalism” and “normativism.” 2 It is difficult to adequately summarize these competing definitions as they constitute an entire field of philosophical analysis (see Bolton, 2001, 2008; Ereshefsky, 2009; Murphy, 2009; Ross, 2005, 2007). Nonetheless, naturalism treats disorder as an objective property, something independent of value judgments and of culture and can be discovered through the scientific method (e.g.…”
Section: The Philosophy Of Defining Disordermentioning
confidence: 99%
“…3 In addition, although I will at times discuss psychiatry in general in order to give a context, most of the ethical issues pertain to certain areas of psychiatry and a few specific purported disorders in particular: namely, those that are on the boundary between normal and abnormal, and are controversial both within the discipline itself and in mainstream culture. Although it is often argued that value-judgments are irreducibly a part of psychiatric classification, 4 and one would be hard pressed to dispute this in general, there is no agreement on which judgments should be considered valid, or even how to assess various types of evidence, specifically with respect to 'laboratory values or other etiological criteria'. 5 It may be that neuroimaging will contribute to discovering the etiology of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%